2021
DOI: 10.1002/cncr.33393
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of tumor‐specific mutations in saliva of patients with oral cavity squamous cell carcinoma

Abstract: BACKGROUND: Oral cavity squamous cell carcinoma (OCSCC) is the most common head and neck malignancy. Although the survival rate of patients with advanced-stage disease remains approximately 20% to 60%, when detected at an early stage, the survival rate approaches 80%, posing a pressing need for a well validated profiling method to assess patients who have a high risk of developing OCSCC. Tumor DNA detection in saliva may provide a robust biomarker platform that overcomes the limitations of current diagnostic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 65 publications
(98 reference statements)
0
21
0
Order By: Relevance
“…( Tables 3 , 4 ) Most of these studies started from Gene Expression Omnibus datasets ( https://www.ncbi.nlm.nih.gov/gds ) in combination with differentially expressed genes, the protein-protein interaction network, gene ontology and the Kyoto Encyclopedia of Genes and Genomes pathway. Shanmugam et al 70 have reported a customized NGS analysis of unique coding regions of seven mutated genes from OSCC saliva, and similar data from whole-exome sequencing were also discovered in tumors from The Cancer Genome Atlas 71 , the International Cancer Genome Consortium gingiva-buccal cohort 69 , and MD Anderson Cancer Center OSCC cohort 72 .…”
Section: Current Cancer Biomarkers Using Ngs-based Techniquementioning
confidence: 76%
See 1 more Smart Citation
“…( Tables 3 , 4 ) Most of these studies started from Gene Expression Omnibus datasets ( https://www.ncbi.nlm.nih.gov/gds ) in combination with differentially expressed genes, the protein-protein interaction network, gene ontology and the Kyoto Encyclopedia of Genes and Genomes pathway. Shanmugam et al 70 have reported a customized NGS analysis of unique coding regions of seven mutated genes from OSCC saliva, and similar data from whole-exome sequencing were also discovered in tumors from The Cancer Genome Atlas 71 , the International Cancer Genome Consortium gingiva-buccal cohort 69 , and MD Anderson Cancer Center OSCC cohort 72 .…”
Section: Current Cancer Biomarkers Using Ngs-based Techniquementioning
confidence: 76%
“…Compared with known genomic salivary biomarkers, such as p53, FAT1, CASP8, PIK3CA, HRAS, NOTCH1, and CDKN2A, NGS-based genomics consider mutation of p53 and promoter hypermethylation of DAPK, TIMP3, p16, and MGMT, cyclone D1 and mammary serine protease inhibitors. Also, up-regulated oncogenic tissue miRNAs and down-regulated tissue suppressive marker miRNAs, including miR 31, miR 125, and miR 3928, are recommended as subjects for further research 70 , 74 , 76 - 79 , 81 . ( Table 5 )…”
Section: Current Cancer Biomarkers Using Ngs-based Techniquementioning
confidence: 99%
“…However, the concordance in saliva was low; indeed, the analysis of TP53 mutations in healthy individuals revealed the presence of pathogenic mutations, which should be taken into account in any subsequent design of ctDNA assays for early diagnosis. Finally, a recent study by Shanmugam et al [33] used massive sequencing techniques to analyse tissue and saliva samples from 121 pre-surgical patients with OSCC. Alterations were identified in more than 95% of these patients, and in more than 97% the alteration was present in saliva, although this concordance was lower in initial disease stages.…”
Section: Ctdna In Oral Cavity Tumoursmentioning
confidence: 99%
“…Most cases (90%) are histologically classified as squamous cell carcinoma. Despite several therapeutic advances in cancer treatment, patients with advanced-stage disease presented a 5-year survival rate varying from ~20 to 60% [ 2 ]. The most significant improvements in survival were described only among patients with nasopharynx and oropharynx cancer [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%